Immature Platelet Counts and Thrombopoietin Plasma Concentrations in Thrombocytopenic and Non-thrombocytopenic Preterm Infants - Sallmon, Hannes; Weimann, Andreas; Bührer, Christoph; Metze, Boris; Dame, Christof; Cremer, Malte (Frontiers in Pediatrics, 2021)
Objective: Immature platelet counts (IPC) may prove useful in guiding platelet transfusion management in preterm neonates. However, the relationship between IPCs and thrombopoietin (Tpo) concentrations has not been evaluated in preterm neonates. Methods: Prospective cohort study in thrombocytopenic (n=31) and non-thrombocytopenic very low birth weight (VLBW) infants (n=38), and healthy term neonates (controls; n=41). Absolute platelet counts (APCs), IPCs, and Tpo concentrations were assessed by a fully-automated hematological analyzer (IPC, APC) and by ELISA (Tpo concentrations) in parallel on day 1 of life (d1), d3, and d7. Results: In healthy term neonates, APCs remained stable between d1 and d3. In non-thrombocytopenic VLBW infants, APCs increased from d1 to d7, while in the thrombocytopenia group, APCs declined from d1 to d3, before they slightly increased again by d7. Median IPCs were similar in healthy term vs. non-thrombocytopenic VLBW infants and remained stable between d1 and d3 (p > 0.05). Notably, IPCs significantly increased between d3 and d7 in both non-thrombocytopenic and thrombocytopenic VLBW infants. However, in thrombocytopenic VLBW infants, IPC values were significantly lower at each time point as compared to non-thrombocytopenic VLBWs (p<0.001). In each subgroup, Tpo concentrations increased from d1 to d3. The median Tpo concentrations were significantly higher in thrombocytopenic as compared to non-thrombocytopenic VLBW infants at d3 (p=0.01) and d7 (p=0.002). Discussion: Term infants, thrombocytopenic and non-thrombocytopenic preterm infants display similar developmental changes in indices of megakaryopoietic activity. In thrombocytopenic preterm infants, however, the responsive increases in Tpo and immature platelets appear to be developmentally limited.